Assessment of RC Bridges integrity by means of low-cost investigations - Flavio Stochino; Maria Luisa Fadda; Fausto Mistretta (Fracture and Structural Integrity)
Infrastructure aging is an important problem nowadays, in particular for countries like Italy in which the main motorways were built 50 years ago. Huge budgets are necessary to keep infrastructure and bridges in service. In addition, the lack of a proper and timely maintenance, entails an increase of the deterioration and therefore higher costs of repair.